Germination, viability and longevity of horseweed (Conyza spp.) seeds as a function of temperature and evaluation periods - Agostinetto,Dirceu (2018)
ABSTRACT: In Brazil, horseweed is one of the most important weeds because of the resistance to herbicides and high competitive for the crops. A large of losses were reported in major crops such as soybeans, wheat and corn, where the use a no-tillage system and the herbicide resistance promote better establishment. A correct understanding of the way temperature influences germination enables the prediction of the regions with the highest potential for colonization by this weed and thus facilitates its control. The objective of this study; therefore, was to discern the ways temperature affected the germination, viability and longevity of horseweed seeds. Testing was done at 10, 20 and 30°C, while evaluation occurred on days 0, 15, 30, 45 and 60. Seeds were packed in a nylon mesh bag (5x5cm), with 10g of upland soil (Yellow Red Argissolo, sandy loam texture), placed in transparent plastic boxes at 0 to 0.5cm soil depth, at the temperatures specified. Percentage of remaining seeds, first and second germination counts, abnormal seedlings, and dead, dormant, viable and non-viable seeds, were assessed. Horseweed seeds achieve secondary dormancy at 10, 20 and 30°C, while their quality and the longevity showed damage at 20 and 30°C temperatures.